Effectiveness of Ethanolic Extract of Aloe Vera Leaves against Staphylococcus aureus: Efektivitas Ekstrak Etanol Daun Lidah Buaya (Aloe vera) terhadap Staphylococcus aureus - Permatasari, Viki Ayu Intan; Nurjanah, Mutia Hariani; Widodo, Wimbuh Tri (Medicra (Journal of Medical Laboratory Science/Technology), 2020)
Since long ago Indonesia used nutritious plants as traditional medicines. Various types of plants in Indonesia can be used as alternative ingredients, one of which is aloe vera. Aloe vera contains saponin and anthraquinone, so aloe vera leaves function as antiseptic and antibacteria. Staphylococcus aureus is a gram-positive coccus bacteria. This bacterium is often found as a normal germ flora in humans. Staphylococcus aureus can cause infections in humans and animals. This study aims to determine the effect of ethanolic extract of Aloe vera leaves in inhibiting Staphylococcus aureus by using maceration extract method. The concentrations used were 20%, 40%, 60%, 80% and 100% with positive control (Erytromycin) and negative control (aquades). The inhibitory zone analysis is done using the table method. Test of ethanol extract of Aloe vera leaves in inhibiting Staphylococcus aureus produced inhibition zones at concentrations of 60%, 80% and 100% with average diameter of 6.94 mm, 6.22 mm and 9.5 mm. The conclusion of this research is the ethanolic extract of Aloe vera leaves can inhibit Staphylococcus aureus in high concentrations